Youth’s mental health journeys through the COVID-19 pandemic using arts-based methods in virtual environments - Roberta L. Woodgate; Lisa Mary-Quigley; Ashley Bell; Marlyn Bennett; Andrew R. Hatala (PLoS ONE, 2026)
Already facing a crisis, youth mental health and well-being has been dramatically affected by the COVID-19 pandemic. Recognizing this decline in youth mental health is expected to last well into the future, there is an imperative to examine youth’s experiences with their mental health journeys throughout with COVID-19 pandemic, which will play a critical role in shaping their future mental health trajectories. Utilizing guidelines developed for using arts-based methods in virtual environments, this interpretive description study aimed to gain deeper insight into youth’s mental health journeys throughout the pandemic. Using open-ended interviews supplemented with youth-directed arts-based methods (ecomaps, journey maps, and creating an art piece of their choosing), thematic analysis was used to identify themes arising from the textual and graphical data. 19 youth (14–24 years) from across Canada shared their journeys with mental health and well-being throughout the COVID-19 pandemic. Based on key time points, three themes were identified: 1) Entering COVID-19: Chaos, 2) During COVID-19: Introspection, and 3) After COVID-19: Personal Growth. Journeying through the COVID-19 pandemic, youth experienced changes in their mental health and well-being experiences. Recommendations provide points to consider in supporting youth mental health and the utilization of arts-based methods to support reflection and introspection.